Skrining dan Uji Efektivitas Reduksi Merkuri Oleh Isolat Bakteri Mangrove - Sulastri, Aini; Jumiati, Jumiati; Desmaiani, Herda (Universitas Tanjungpura, 2024)
A poor metal waste disposal system increases the concentration of heavy metals in the environment, causing pollution. Reducing the concentration of heavy metal pollution can be done one way by bioremediation using bacteria. Exploratory research on mangrove bacteria shows that bacterial isolates have been successfully isolated and have the ability to grow on media containing mercury. In this research, further tests will be carried out in the form of screening and testing the effectiveness of mercury metal reduction. This research aims to find isolates that have a high ability to grow in environments containing mercury, and the effectiveness of reducing mercury metal by these bacteria. This basic research will be the beginning of the development of effective microorganisms as bioremediation agents. This research consisted of two stages, namely screening the best bacterial isolates and testing the effectiveness of mercury metal reduction. The research results showed that isolates B27, S04 and S23 were the best isolates in being able to remove mercury concentrations of up to 99.99%. This research is ongoing research which has the output as a first step in obtaining Effective Microorganisms which can later become products and can be applied as a method to improve environmental quality.